Legal Legitimacy and Recognition of Madrasah Diniyah Mu’adalah Education in Indonesia: A Review of Law No. 18 of 2019 - Nurul Istiqomah; Ahmad Arifi (FKIP - Universitas Riau, 2026)
Pesantren and madrasah diniyah mu’adalah (MDM) have long served as pillars of Islamic education in Indonesia, yet their legal standing within the national education system remained ambiguous prior to 2019. This study aims to analyze the legal legitimacy, implementation mechanisms, and policy implications of Law No. 18 of 2019 on pesantren for the formal recognition of MDM in Indonesia. Using a library research method with a normative juridical and content analysis approach, this study examined the full statutory text of Law No. 18/2019, ministerial implementing regulations, official government documents, and relevant academic literature. The findings reveal that the law establishes multi layered legitimacy for MDM across eight articles, covering functional, typological, structural, and autonomy based dimensions. However, a significant implementation gap exists between the inclusive spirit of the law and the selective mechanisms of its implementing regulations (PMA No. 31/2020), which disproportionately benefit larger, better resourced pesantren. This study concludes that the principle of recognition without assimilation must be consistently applied in all derivative policies, and that empowerment based regulatory approaches are essential to ensure equitable legal recognition for MDM institutions across all regions of Indonesia.